Histone deacetylase inhibitors impair the host immune response against Mycobacterium tuberculosis infection. (September 2019) - Zhu, Chuanzhi; Cai, Yi; Zhu, Jialou; Zhang, Lanyue; Xing, Aiying; Pan, Liping; Jia, Hongyan; Mo, Siwei; Feng, Carl G.; Shen, Hongbo; Chen, Xinchun; Zhang, Zongde
Abstract: Histone deacetylase inhibitors (HDACi), a novel class of anti-cancer drug, have been recently reported to suppress host immunity and increase susceptibility to infection. Tuberculosis, a leading infectious disease killer caused by Mycobacterium tuberculosis ( M.tb ), is basically the product of the interaction between bacterial virulence and host resistance. However, the effects of HDACi in host immunity against M.tb is largely unknown. In this study, we found that HDACi including Trichostatin A (TSA) and suberoylanilide hydroxamic acid (SAHA) significantly impaired phagocytosis and killing activity of macrophage. In line with these findings, we noted that M.tb induced reactive oxygen species (ROS) production and autophagy are significantly suppressed by TSA. Transcriptome analysis revealed that the suppression of autophagy by TSA might due to its inhibiting autophagy-regulating genes such as CACNA2D3, which regulates intracellular Ca 2+ levels. Finally, we confirmed that HDACi including TSA and SAHA significantly exacerbated the histopathological damage and M.tb load in the lung of M.tb infected mice. Taken together, our results indicated that HDACi at least TSA and SAHA significantly impaired macrophage immunity against M.tb and therefore increase susceptibility to TB, our findings raised the concern that the potential side effects of HDACi on latent TB reactivation should be considered in clinic.